2018
DOI: 10.1111/petr.13319
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis is a sign of poor outcome in pediatric Epstein‐Barr virus‐associated post‐transplant lymphoproliferative disease after allogeneic hematopoietic stem cell transplantation

Abstract: EBV-related PTLD developing after HSCT is a potentially life-threatening disease.HLH is uncommon after allogeneic HSCT. Data on outcome of patients with PTLD and concomitant HLH after allogeneic HSCT are limited. In this retrospective study, we collected demographic, clinical, laboratory, and outcome data for 408 patients who underwent allogeneic HSCT from 2006 to 2015. Graft source included CB (n = 135; 33.1%), PBSCs (n = 34; 8.3%), and BM (n = 239; 58.6%). Eight out of 408 patients (2%) developed EBV-PTLD wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…One retrospective study showed high mortality (37.5%) in EBV PTLD within 100days post-transplant and all deceased patients developed HLH manifestations. 8 The presented case also responded initially with tapering of immunosuppression, high dose steroid and weekly rituximab with chemotherapy directed against HLH but ultimately died on day +137 post-transplant.…”
Section: Discussionmentioning
confidence: 82%
“…One retrospective study showed high mortality (37.5%) in EBV PTLD within 100days post-transplant and all deceased patients developed HLH manifestations. 8 The presented case also responded initially with tapering of immunosuppression, high dose steroid and weekly rituximab with chemotherapy directed against HLH but ultimately died on day +137 post-transplant.…”
Section: Discussionmentioning
confidence: 82%
“…For the same risk factors explored in both studies, those from Kalra et al [67] were retained as the analyses were done on a larger sample. In addition, the Ali et al [31] and Althubaiti et al [32] studies were carried out with non-disjoint samples, but both were retained because different variables were explored. The reasons for exclusion of these articles were as follows: Two articles were excluded because their sample is a subset of the sample from two other articles.…”
Section: Resultsmentioning
confidence: 99%
“…The method used to diagnose PTLD was not detailed in one study. The length of follow-up was an important source of variation between studies; in some cases the follow-up period was not reported [31,32,34,40,46,48,52,55,59,61,63,73,81,83,86,90,94,98,100].…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Asano et al 10 reported that secondary HLH developed in 37 out of 5427 HSCT cases, and four out of 37 were PID. Ali et al 11 reported EBV-associated HLH in three out of 408 patients who underwent allogeneic HSCT, and all three patients died. Epstein-Barr virus is the most frequently associated infectious agent with HLH.…”
Section: Discussionmentioning
confidence: 99%